2017
DOI: 10.3892/etm.2017.4457
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological postconditioning with atorvastatin calcium attenuates myocardial ischemia/reperfusion injury in diabetic rats by phosphorylating GSK3β

Abstract: Diabetes is an independent risk factor for myocardial ischemia, and many epidemiological data and laboratory studies have revealed that diabetes significantly exacerbated myocardial ischemia/reperfusion injury and ameliorated protective effects. The present study aimed to determine whether pharmacological postconditioning with atorvastatin calcium lessened diabetic myocardial ischemia/reperfusion injury, and investigated the role of glycogen synthase kinase (GSK3β) in this. A total of 72 streptozotocin-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…Meanwhile, plasma CK-MB and LDH levels in the DM-DW group were increased compared to the DM-D group, suggesting that cardioprotection of DEX were suppressed by Wort. However, the aforementioned index in the DM-S group was similar to the S group, and no significant difference was observed between DM-S and S groups, indicating that a 4-week diabetic state may not significantly influence cardiac function, which was consistent with a previous study [ 25 ], while Mokhtari et al reported that STZ-induced diabetes at the 10th week significantly increases the level of cTnI and exacerbates the myocardial injury [ 26 ]. Besides, prior studies have noted that a diabetic heart is more sensitive to ischemic injury [ 26 , 27 ], while Aasum et al [ 28 ] have reported that the in vitro diabetic rat heart was less sensitive to myocardial I/R injury 6 weeks after STZ administration, while at 12th week, cardiac function was significantly impaired.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Meanwhile, plasma CK-MB and LDH levels in the DM-DW group were increased compared to the DM-D group, suggesting that cardioprotection of DEX were suppressed by Wort. However, the aforementioned index in the DM-S group was similar to the S group, and no significant difference was observed between DM-S and S groups, indicating that a 4-week diabetic state may not significantly influence cardiac function, which was consistent with a previous study [ 25 ], while Mokhtari et al reported that STZ-induced diabetes at the 10th week significantly increases the level of cTnI and exacerbates the myocardial injury [ 26 ]. Besides, prior studies have noted that a diabetic heart is more sensitive to ischemic injury [ 26 , 27 ], while Aasum et al [ 28 ] have reported that the in vitro diabetic rat heart was less sensitive to myocardial I/R injury 6 weeks after STZ administration, while at 12th week, cardiac function was significantly impaired.…”
Section: Discussionsupporting
confidence: 85%
“…The phosphorylation of Akt in the DM-S group was not different from the S group, which was not consistent with the Wang et al study, which reported that the signaling pathway was impaired in the diabetic myocardium, with a lower level of basal Akt phosphorylation than normal rats [ 27 ]. The phosphorylation of GSK-3 β was decreased in the DM-S group compared with the S group, suggesting that p-GSK-3 β was inactivated in the diabetic state, which was confirmed by a prior study [ 25 ]. Mokhtari et al [ 26 ] confirmed that at the 10th week of diabetes induction, phosphorylation of GSK-3 β in the DM-I/R group was significantly less than the I/R group, suggesting that diabetes impairs the intracellular signaling pathways and increases cardiac injury as compared to normal hearts; however, no significant difference was seen between I/R and DM-I/R groups in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Presently, a large number of studies have reported that HSP70 is induced by preconditioning, including IPC (Hampton et al, ), RIPC (Vicencio et al, ), LPS (Shimizu et al, ), pharmacological (S. Guo, Gao, et al, 2018), and physical preconditioning (Uryash et al, ) and serves as a key mediator enhancing myocardia stress adaption to I/R injury (Figure ). In addition, postconditioning has also been revealed to alleviate I/R injury via inducting HSP70 (L. Chen, Cai, Cheng, Zhang, & Fang, ). Hereinafter, we mainly focus on HSP70‐induced cardioprotective effects against I/R injury in the presence of preconditioning and postconditioning.…”
Section: Hsp70: Involvement In Conditioning Against Myocardial I/r Inmentioning
confidence: 99%
“…Nonetheless, there are some reports of preserved protection in models of T1DM, including exercise [ 136 ] and ischemic preconditioning [ 86 ], while Potier et al [ 108 ] identify a specific shift to protective efficacy of B2 bradykinin receptors in T2DM hearts (vs. B1 receptors in non-DM tissue). Atorvastatin is also reportedly cardioprotective in T1DM rats [ 137 ], involving a glycogen synthase kinase 3β (GSK3β) dependent protection linked to heat shock factor 1 and heat shock protein 70 (HSP70).…”
Section: Diabetes Impacts Myocardial Ischemic Tolerance and Cardiopromentioning
confidence: 99%